The Effect of Knowledge Sharing, Wages, Occupational Safety and Health (K3) on The Performance of Project Workers On CV. Airlangga Hutama Consultant Madiun - Dwi Kuncoro, Wahyu; Rapini, Titi; Sujiono (JENIUS (Jurnal Ilmiah Manajemen Sumber Daya Manusia), 2026)
This study aims to analyze the Influence of Knowledge Sharing, Wages, Occupational Safety and Health (K3) on the Performance of Project Workers on Cv. Airlangga Hutama Consultant Madiun. This study applied a quantitative approach using a sample of primary data from 55 respondents, namely all project workers Cv. Airlangga Hutama Madiun. The results of the study showed that partially sharing knowledge, wages, and K3 had a positive and significant effect on worker performance. Wages were the most dominant variable with the highest regression coefficient, followed by knowledge sharing and K3. Simultaneously, these three variables also had a significant effect on the performance of workers with a determination coefficient value of 80.1%, which shows that the research model has strong explanatory abilities.